2010
DOI: 10.1111/j.1469-8137.2010.03532.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple climate change factors on the tall fescue–fungal endophyte symbiosis: infection frequency and tissue chemistry

Abstract: Summary• Climate change (altered CO 2 , warming, and precipitation) may affect plantmicrobial interactions, such as the Lolium arundinaceum-Neotyphodium coenophialum symbiosis, to alter future ecosystem structure and function.• To assess this possibility, tall fescue tillers were collected from an existing climate manipulation experiment in a constructed old-field community in Tennessee (USA). Endophyte infection frequency (EIF) was determined, and infected (E+) and uninfected (E)) tillers were analysed for ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 48 publications
6
74
4
2
Order By: Relevance
“…This result obtained in the field agrees with data obtained in controlled conditions demonstrating the lack of effect of high temperatures on total ergot contents in tall fescue. 34 Finally, this suggests that, during this assay, the correlation observed between ergovaline content in the whole plant and cumulative degree-d is due to an effect of temperature on plant growth. Cumulative rainfall from the beginning of February to the fully ripe stage plotted against ergovaline concentrations in the whole plant showed major differences between years ( Figure 4B).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result obtained in the field agrees with data obtained in controlled conditions demonstrating the lack of effect of high temperatures on total ergot contents in tall fescue. 34 Finally, this suggests that, during this assay, the correlation observed between ergovaline content in the whole plant and cumulative degree-d is due to an effect of temperature on plant growth. Cumulative rainfall from the beginning of February to the fully ripe stage plotted against ergovaline concentrations in the whole plant showed major differences between years ( Figure 4B).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Although it has been suggested that a limited supply of water could increase alkaloid production, 23 this result in the field agrees with data obtained under controlled conditions, demonstrating the lack of effect of water availability on total ergot contents in tall fescue. 34 In conclusion, this study demonstrates for the first time that around 60% of wild tall fescue is infected with Epichloe in southern France and that most of the infected plants are able to produce very high ergovaline levels in seeds. Determination of ergovaline contents in Kentucky 31 tall fescue infected with E. coenophiala at different growth stages revealed that the levels in plant can be high and do not markedly differ from levels measured in other countries where fescue toxicosis has been reported.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…precipitation: Hawkes et al 2011); & with multiple climate change factors (Paajanen et al 2011); & in relation to endophytes and viruses, two key factors for plant health (Jones 2009;Brosi et al 2010); & in relation to mycorrhiza diversity and productivity (Deslippe et al 2010;Egli 2011); & with long-term datasets (Hannukkala et al 2007;Fitt et al 2011 & and considering various plant disease control methods (Ghini et al 2011a). …”
Section: Plant Health and Climate Change: Conclusion And Research Gapsmentioning
confidence: 99%
“…Changes in the composition of plant-associated microbial communities have often been associated with plant physiology (9), health (14), and environmental perturbances (11). In the present study, we examined fungal endophytic communities in grapevines using both cultivation-based and cultivation-independent approaches.…”
mentioning
confidence: 99%